Social Entrepreneurship and Women Empowerment : A Case Study of Peepal Tree Organisation - P., Chythra; A. B., Gangu (AMC Indian Journal of Entrepreneurship, 2021)
Social entrepreneurship ventures in India give solutions to many problems. The main problem in India is empowerment of women, where social entrepreneurship ventures are trying to empower women. This study focussed on barriers to women empowerment, the elements of women empowerment defined by European Institute of Gender Equity (EIGE), and the case of Peepal Tree Foundation (PTF) which is trying to empower women. The PTF as a social enterprise provides training to women that enables them to produce products. It empowers women with economic security, entrepreneurial quality, and educational knowledge.